Dr. James C. Sternberg (1980)
Dr. James C. Sternberg (1927-2001) was the Vice President of Advanced Research at Beckman Instruments and responsible for the development of the Glucose Analyzer in the 1970. In 1968 he published a landmark paper on a new method of measuring glucose quickly using glucose oxidase, which was the basis for the technology behind the Beckman Instruments Glucose Analyzer. This work was the launching point for his other innovations using electrochemical methods for the measurement of blood urea nitrogen, chloride, carbon dioxide, cholesterol, and uric acid.
Keywords: Scientists--Portraits; Beckman, Arnold O.; Beckman Instruments, Inc.